THE EFFECT OF MOTIVATION AND COMPETENCE ON EMPLOYEE PERFORMANCE IN SATELLITE TECHNOLOGY CENTER - NATIONAL INSTITUTE AERONAUTICS AND SPACE - Sujiati, Sujiati; Ma'arif, M. Syamsul; Najib, Mukhamad (Jurnal Aplikasi Manajemen, 2017)
This study aims toanalyze the effect of motivation and competency factor on employee performance in Satellite Technology Center-National Institute of Aeronautics and Space. This study uses a quantitative approach using descriptive analytic surveywith cross-sectional study. Respondents in this study of 79 people who are employees of part dissemination, program and facility, administration.The data analysis used in this research were descriptive analysis and Structural Equation Modeling (SEM) PLS. The results show that motivationhas significant effect either directly or indirectly through the competency on employee performance in Satellite Technology Center-National Institute of Aeronautics and Space.